Examination of early adaptation of newborns small for gestational age - Noveski Zlatko (Medicinski fakultet Priština, Društvo lekara Kosova i Metohije Srpskog lekarskog društva, 2021)
Introduction: Children with low body weight for gestational age are five times more likely to die in the neonatal period and 4.7 times more likely to die in the first years of life compared to children born at term. The aim To analyze early adaptation to extrauterine life of low body weight for gestational age. Material and methods: Retrospective study with the observation period January-September 2018. The data were obtained by reviewing the medical histories of newborns. As parameters of early adaptation, we observed the Apgar score in the 1st and 5th minute as well as the presence of polycythemia at birth. Results: Out of a total of 405 newborns, 52 had low body weight for gestational age. Apgar score in the 1st and 5th minute was statistically significantly lower in children small for gestational age compared to children with normal body weight for gestational age (p <0.05). Polycythemia is a mechanism of adaptation statistically significantly more often present in children of small body weight for gestational age (p <0.05). Conclusion: Children of low body weight for gestational age have a lower Apgar score in the first and fifth minutes as well as more frequent polycythemia compared to children with normal body weight and we can take them as good indicators of adaptation to early extrauterine life.